Direct Sulfamidation of Alcohols Using Magnetically Recoverable Pd/Fe3O4 as the Catalyst - Siva Prasad, Aviraboina; Satyanarayana, Bollikonda (Asian Journal of Chemistry, 2012)
An efficient method is described for the direct amination of alcohols with sulfonamides using magnetically separable Pd/Fe3O4 as a catalyst without using any additives. Various alcohols such as benzylic alcohol and allylic alcohol underwent sulfamidation with sulfonamides gave the corresponding products in good to excellent yields. This effective catalyst requires no preactivation of the hydroxy group of alcohols and the reaction is environmentally benign with water as a by-product. The catalyst is completely recoverable with the simple application of an external magnetic field and the efficiency of the catalyst remains unaltered even after five cycles.